From Samuela 'Akilisi Pohiva - 'Akilisi Pohiva (Asia Pacific Network, 1996)
On 23 August 1996, all the nine People's Representatives met and agreed to submit to the Parliament of Tonga a petition for the impeachment of the Minister for Justice and Attorney-General Tevita Poasi Tupou based on Section 75 of the Constitution.